2013
DOI: 10.1542/peds.2012-2585
|View full text |Cite
|
Sign up to set email alerts
|

Galactose-α-1,3-galactose and Delayed Anaphylaxis, Angioedema, and Urticaria in Children

Abstract: A novel form of anaphylaxis and urticaria that occurs 3 to 6 hours after eating mammalian meat is not uncommon among children in our area. Identification of these cases may not be straightforward and diagnosis is best confirmed by specific testing, which should certainly be considered for children living in the area where the Lone Star tick is common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 32 publications
5
73
2
4
Order By: Relevance
“…Only a minority of patients with cetuximab allergy (22.2%) vs 62.5% of those with delayed red meat allergy recalled tick bites. These percentages are lower than those reported by Commins et al (10), who found that more than 90% of subjects with serum IgE to α-Gal had a history of tick bites, and by Kennedy et al (22), who reported in a paediatric population with delayed anaphylaxis to red meat a tick exposure in 100% of cases. A possible explanation for this fact might be that, unlike subjects exposed to Amblyomma americanum, subjects exposed to Ixodes ricinus are not always aware of being bitten, as during the attachment and feeding process Ixodes ricinus injects a complex mixture of bioactive chemicals into the host, eventually resulting in a painless bite.…”
Section: Discussioncontrasting
confidence: 56%
“…Only a minority of patients with cetuximab allergy (22.2%) vs 62.5% of those with delayed red meat allergy recalled tick bites. These percentages are lower than those reported by Commins et al (10), who found that more than 90% of subjects with serum IgE to α-Gal had a history of tick bites, and by Kennedy et al (22), who reported in a paediatric population with delayed anaphylaxis to red meat a tick exposure in 100% of cases. A possible explanation for this fact might be that, unlike subjects exposed to Amblyomma americanum, subjects exposed to Ixodes ricinus are not always aware of being bitten, as during the attachment and feeding process Ixodes ricinus injects a complex mixture of bioactive chemicals into the host, eventually resulting in a painless bite.…”
Section: Discussioncontrasting
confidence: 56%
“…The same patients tolerized chicken, turkey or fish because poultry and fish do not express α‐gal, a carbohydrate common in nonprimate mammals. Most reports on this new form of α‐gal‐mediated delayed‐type meat allergy included individuals living in south‐eastern regions of the United States 8, 9, 10. These data were complemented by reports on Australian and more lately also Swedish patients 11, 12.…”
mentioning
confidence: 99%
“…Onset is typically in adults, although children are not excluded. 4,14 Kennedy et al 18 identified 45 pediatric patients with the allergy. In the United States, red meat typically includes beef, pork, and lamb.…”
Section: Diagnostic Approachmentioning
confidence: 99%